Unmet needs of bipolar disorder patients - Hajda M (Dove Medical Press, 2016)
Miroslav Hajda,1 Jan Prasko,1 Klara Latalova,1 Radovan Hruby,2 Marie Ociskova,1 Michaela Holubova,1,3 Dana Kamaradova,1 Barbora Mainerova1 1Department of Psychiatry, Faculty of Medicine and Dentistry, Palacky University Olomouc, University Hospital Olomouc, Olomouc, Czech Republic; 2Outpatient Psychiatric Department, Martin, Slovak Republic; 3Department of Psychiatry, Regional Hospital Liberec, Liberec, Czech Republic Background: Bipolar disorder (BD) is a serious mental illness with adverse impact on the lives of the patients and their caregivers. BD is associated with many limitations in personal and interpersonal functioning and restricts the patients’ ability to use their potential capabilities fully. Bipolar patients long to live meaningful lives, but this goal is hard to achieve for those with poor insight. With progress and humanization of society, the issue of patients’ needs became an important topic. The objective of the paper is to provide the up-to-date data on the unmet needs of BD patients and their caregivers. Methods: A systematic computerized examination of MEDLINE publications from 1970 to 2015, via the keywords “bipolar disorder”, “mania”, “bipolar depression”, and “unmet needs”, was performed. Results: Patients’ needs may differ in various stages of the disorder and may have different origin and goals. Thus, we divided them into five groups relating to their nature: those connected with symptoms, treatment, quality of life, family, and pharmacotherapy. We suggested several implications of these needs for pharmacotherapy and psychotherapy. Conclusion: Trying to follow patients’ needs may be a crucial point in the treatment of BD patients. However, many needs remain unmet due to both medical and social factors. Keywords: bipolar disorder, unmet needs, stigma, treatment, medication, quality of life, family, psychotherapy